Unlocking Opportunities: Learning Beyond Experience Trough Benchmarking from UMT to UAD - Nargis - Nargis; Desmi Ayu Cintya; Mita - Melyana; Yunita - Lintang; Novi - Cintya; Riana Andriana Putri (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
AbstractBenchmarking is an activity in education that is carried out to compare various aspects of two or more institutions within an educational institution, be it a school, university or other educational institution. The activity was carried out by a group of students from Muhammadiyah University, Tangerang, and Ahmad Dahlan University, Yogyakarta. In this comparative study activity, students took part in a workshop with the theme "Building a Relationship and Giving Experience for Each Other to Improve English Skill Performance". Using the observation method, the researcher explains the social and cultural in Yogyakarta. Yogyakarta is a popular tourist destination and university town, which leads to a wide range of linguistic and cultural variances brought about by the city's large immigrant and visitor populations. Both locals and visitors respect each other's culture and the way the people of Yogyakarta are cultured, despite the stark disparities in language, ethnicity, and customs.Keywords: Socio-cultural, facilities, benchmarking.